MODERN TRENDS AND FEATURES OF TOURISM SECTOR DEVELOPMENT IN UZBEKISTAN (Journal of Academic Research and Trends in Educational Sciences, 2024)
The article examines the growth of the tourism sector, which is determined by a number of factors, including what new opportunities are available for the development of tourism, including investment attraction, infrastructure modernization, the development of cultural tourism and the improvement of business conditions, c-tourism and the impact on the economy.